2020
DOI: 10.1093/poq/nfaa044
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Willingness to Share Smartphone-Sensor Data

Abstract: The growing smartphone penetration and the integration of smartphones into people’s everyday practices offer researchers opportunities to augment survey measurement with smartphone-sensor measurement or to replace self-reports. Potential benefits include lower measurement error, a widening of research questions, collection of in situ data, and a lowered respondent burden. However, privacy considerations and other concerns may lead to nonparticipation. To date, little is known about the mechanisms of willingnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
74
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(84 citation statements)
references
References 31 publications
8
74
2
Order By: Relevance
“…Struminskaya et al found similar results in their study [ 32 ], where they tested hypotheses comparing WTP for universities, statistical offices, and market research companies. They found that the WTP reported by respondents is significantly highest for universities, followed by statistical offices and finally for market research firms.…”
Section: Introductionsupporting
confidence: 52%
See 3 more Smart Citations
“…Struminskaya et al found similar results in their study [ 32 ], where they tested hypotheses comparing WTP for universities, statistical offices, and market research companies. They found that the WTP reported by respondents is significantly highest for universities, followed by statistical offices and finally for market research firms.…”
Section: Introductionsupporting
confidence: 52%
“…Trust in the institution collecting the data was found to be a key factor in the willingness to share data [ 21 , 31 , 32 ]. Several studies have examined the researching institution’s role on willingness to share passive data.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…While hypothetical compliance refers to respondents' general disposition to participate in a task, observed compliance, in contrast, refers to respondents' actual participation in a task. Empirical findings indicate that respondents' hypothetical compliance tends to be higher than their observed compliance with a task ( 21 , 22 ). Following this relation between hypothetical and observed compliance, we address the following research question: Do hypothetical and observed compliance rates with fitness tasks in a self-administered smartphone survey differ from each other (RQ1)?…”
Section: Research Questionsmentioning
confidence: 99%